Høygud og kulturbringer - til Werner Müllers forståelse av de sentrale skogindianeres religioner - Breivik, Nils Olav (Religionsvidenskabeligt Tidsskrift, 1988)
Werner Müller is one of the leading European scholars on North American Indian religions, with numerous, albeit somewhat controversial, works, primarily in German. According to Müller, the Indian Supreme God and Culture Hero, which is the topic of this paper, both have a cosmic structure. The Supreme God simply is the cosmos itself, integrating man and cosmos in total unity. In the figure of the Culture Hero, the focus in on man’s individuality within cosmos, but also transcending it. Consequently, Müller finds that the Supreme God and the Culture Hero represent different types of religiosity in Indian life. This is clearly seen in the Central Woodland area. This area brings to the fore primary creative forces in North American Indian religions, thereby also illustrating the underlying structures of Indian mentality. Müller’s strong focus on the irrational and pictorial character of Indian mentality brings him in opposition to dominant anthropological theories, but nevertheless deserves reconsideration for further development of research.